2020
DOI: 10.3390/su12010376
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Better the Influential Factors of Commuters’ Multi-Day Travel Behavior: Evidence from Shanghai, China

Abstract: Alleviating traffic congestion and developing sustainable transportation systems in a city can be assisted by promoting environmentally friendly transportation modes such as walking, cycling, and public transport. Strategies for promoting these desirable transportation modes can be identified based on a sound understanding of how commuters choose travel modes. In this study, multi-day commuting travel mode data was used to explore factors that influenced commute mode choice. A multinomial logit model and a bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The transit service quality needs to meet the demand of potential travelers. A study revealed that traveler's age, gender, and marital status have an indirect influence on commuter's mode choice and the costs incurred due to number of transfer points and distance to the nearest transit stations are significant factors that hinder commuters from selecting the public transit system [31]. Fare reduction and other associated incentives are effective in promoting the use of public transportation [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transit service quality needs to meet the demand of potential travelers. A study revealed that traveler's age, gender, and marital status have an indirect influence on commuter's mode choice and the costs incurred due to number of transfer points and distance to the nearest transit stations are significant factors that hinder commuters from selecting the public transit system [31]. Fare reduction and other associated incentives are effective in promoting the use of public transportation [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2) Legislation: the traffic routing policies and the extent of stringent measures taken to administer the functioning of the unconventional modes of transport also influence vehicle mode choice. [20]. e ecological dimension is captured by the factor of environmental pollution [21].…”
Section: Legal Factorsmentioning
confidence: 99%
“…All these strategies and decisions go through the identification of user preferences regarding communication routes, transportation methods, and consumption habits, among others. That is why the use of tools such as simulation, optimization, and machine learning, is a fundamental aid for the decision-making process [9]. Figure 1 shows the time evolution, since 2010, of the number of Scopus-indexed articles that contain in their title or abstract the combination of words "sustainable transportation" (or "sustainable transportation") and each of the following combinations: "machine learning" or "artificial intelligence", "optimization", "simulation", or "fuzzy".…”
Section: Introductionmentioning
confidence: 99%